Integrating AI-Powered Reading Tools in ESP: Effects on Students’ Digital Reading Literacy and Critical Thinking Skills - Sasabone, Luana; Taufiq, Anwar; Sendana, Aris Kaban; Rusliana, Rusliana; Sahraeny, Sitti (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Digital reading literacy and critical thinking are essential in ESP learning because students are required to critically understand, evaluate, and interpret specific digital texts relevant to their academic and professional fields. This study aims to analyze the effect of the integration of AI-powered reading tools in learning English for Specific Purposes (ESP) on the ability of digital reading literacy and critical thinking skills of students. This research employed a quantitative methodology utilizing a quasi-experimental design with two groups: an experimental group of 30 students and a control group of 30 students in the accounting study program. The experimental group utilized that integrated AI-powered reading tools such as ChatGPT, Spreeder and Perplexity AI, whereas the control group employed traditional learning methods. The data was gathered using a pretest and posttest aimed at assessing students' digital reading and critical thinking abilities. Data analysis was performed utilizing SPSS Statistics 26, employing descriptive statistical methods, an independent samples t-test, and effect size (Cohen’s d). The findings indicated that both groups exhibited growth, although the experimental group showed a more pronounced increase compared to the control group. The independent sample t-test findings revealed a significant difference in posttest scores between the two groups (p < 0.05), indicating that AI-powered reading tools effectively enhance student learning outcomes, especially in critical thinking skills and digital reading literacy. Furthermore, the effect size research indicates that the implementation of AI technology significantly enhances student capabilities. This study concludes that using AI in ESP learning can effectively enhance students' digital reading proficiency and critical thinking abilities. The implications of this research indicate that the integration of AI in ESP learning can be an effective strategy to improve students' digital reading literacy and critical thinking skills.